Originally Posted by

**allyourbass2212** When using the formula$\displaystyle A=\frac{1}{2}(a+b)h$ when solving for b this equals

$\displaystyle \frac{2}{h}(A-\frac{ah}{2})=b$ why do we not distribute the $\displaystyle \frac{2}{h}$ over the parenthesis?

If we were to distribute it I think it would look like this, please correct me if I am mistaken.

$\displaystyle

\frac{A}{1}*\frac{2}{h}-\frac{ah}{h}*\frac{2}{h}=\frac{2A}{h}-a=b$, if this is correct the book does not list it as an answer choice.

Thank you